Os rastros em trânsito: disputas de sentido nos processos de apropriação e reapropriação de discursos do Papa Francisco - Mattana, Bruna (Universidade do Vale do Rio dos Sinos, 2020)
This Master's research is created within the scope of mediatization studies and analyzes how disputes of meaning are configured in the processes of appropriation and re-appropriation of Pope Francis' discourse. Our interest came from the notorious visibility that the pontiff's speeches and attitudes have in the media, since he took the lead in the Catholic Church in March 2013. To understand this phenomenon, we used the concept of circulation - which we understand as a place for discussions - and, with the studies of Braga (2008) and Guinzburg (1989), we started our methodological path in search of evidence that would help us to make inferences, through our contact with the empirical object. After this process, we arrived at our research case, which consists of three episodes. Each of them involves the religious speech made by the Pope, the reverberation of his speech in journalistic articles and the appropriation of the speech by social actors. Our selection process is based on the theme, publicization and affectation of these texts. In an attempt to find the disputes of meaning in the process of circulation of Pope Francis' discourse, we began to analyze the marks and operations of each of these discourses - religious, journalistic and also of social actors. For this, we use the concepts of circulation (ROSA, 2016; FERREIRA, 2013; FAUSTO NETO, 2006, 2018; VERÓN, 2013); fields, circuits and flows (BRAGA, 2017); uses, appropriations and phage (PROULX, 2016; ROSA, 2016, 2019); discourse and its operations (VERÓN, 2004; FAIRCLOUGH, 2001) and reading contracts (ECO, 1987; FAUSTO NETO, 2002, 2010). In this process, we made a discovery that gave a new direction to research: the trails in transit. What we have evidenced is that there are gaps, losses and gains of meaning as this text moves. In this way, discursive phages happen. This term was created by us based on the notion of phagy proposed by Rosa (2016), in order to conceptualize the additions, editions, suppressions and elaborations that occur in the transit of the papal discourse. We also found that the Pope's speech has a totemic characteristic. In other words, excerpts from his speech, sometimes just a sentence, are “pinned” from the original context and, alone, continue to reverberate and gain different consequences, as they have a social character. These aspects of speech management are part of the creative uses that are given to him. That is, they are part of the appropriations made from this text.
Keywords: Papa Francisco; Midiatização; Circulação; Fagia discursiva; Apropriação; Pope Francis; Mediatization; Circulation; Discursive phage; Appropriation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação